(untitled) (Khairulummah, 2025)
This article provides an overview of the history of Waqf, exploring its origins in Islam, when it became a formal institution, and which Muslim rulers significantly promoted Waqf during their reigns. The purpose of this article is to understand when this institution emerged in Islam, how it developed over time, and what changes it underwent. The history of Waqf is examined in different periods, such as:Waqf before Islam ,History of Waqf in Islam, including Waqf in the Prophetic Era Waqf in the Era of the Companions Waqf in the Era of the Rightly Guided Caliphs Waqf in the Umayyad Era Waqf in the Abbasid EraWaqf in the Fatimid Era Waqf in the Ottoman EraWaqf in the Indian Subcontinent. Each period is reviewed separately to provide a comprehensive understanding of Waqf’s historical development.